Marketing Difference: Two Teachable Moments at the Intersection of the Neoliberal University and Geopolitics - Blanka Nyklová (Gender a Výzkum)
This article looks at the effects the neoliberal university has on feminist pedagogy when it is practised in a programme that stresses geopolitical differences. The material for the study comes from my experience as a teacher of a gender studies class for a US study abroad programme based in Prague, Czech Republic. The richly researched paradoxes of doing feminist pedagogy in the neoliberal university assume firm contours when the geopolitical location of both those ‘teaching’ and those ‘taught’ becomes the focus and indeed the ‘commodity’ to be sold. In my article, I focus on my situation as a teacher in an increasingly precarious educational environment in the Czech Republic, exacerbated by the specific framing of the US-based programme and its economic-moral rationality. I reflect on the ethical discontents inadvertently produced by the teaching experience and related commodification of ‘difference’. I argue that the geopolitical context of that commodification is crucial for understanding the local forms and impact of the neoliberal university. The contested standing of gender studies in the Czech Republic, which has been shown to stem in part from the post-1989 developments, intersects with the reform of the Czech science system. By exploring how this setting affects the micro-level of class dynamics and lesson content I show that there is a need to study the repercussions of the neoliberal university as geopolitically located.